Unleashing the glow: upconverting nanoparticles recharge persistent luminescent materials applications in 3D-printing and optical coding - Drozdowski, Adrian; Poelman, Dirk; Runowski, Marcin; Hemmerich, Hanoch; Rivera-Lopez, Fernando; Grzyb, Tomasz (The Royal Society of Chemistry, 2024)
Persistent luminescence (PersL) materials show long-lasting emission after irradiation with excitation light. Usually, to obtain PersL, excitation with ultraviolet (UV) or visible light is necessary, which limits the use of this phenomenon when the material is in a non-transparent medium for excitation light. A solution to this problem comes from upconverting nanoparticles (UCNPs), which convert near-infrared light, usually not absorbed by such media as polymers or biological tissues, to higher-energetic UV photons, recharging the PersL phosphors. In this article, we report composite materials consisting of PersL phosphor and UCNPs, i.e. SrAl2O4:Eu2+ or ZnGa2O4:Cr3+ and upconverting LiYbF4:Tm3+@LiYF4 core@shell nanoparticles. These materials show dual-emission properties - bright upconversion from near-infrared (NIR at 975 nm) to ultraviolet (UV at 347 nm) and long-lasting PersL in the visible light range. The obtained composite materials present intense, persistent luminescence after the NIR laser excitation. This article proves efficient energy transfer from UCNPs to PersL phosphor and opens new possibilities in the design and synthesis of composite materials. By employing the high-resolution 3D-printing technology, we experimentally confirmed the possibility of multi-modal optical information storage by applying the synthesized materials, developing multi-dimensional microstructured patterns with QR code, letters and first bi-modal, single- and double-layered 8-bit codes based on the combination of PersL and upconversion emission.